Lipid profile pattern in controlled and uncontrolled diabetic patients in a tertiary care centre - Gupta, Smita; Mangal, Rajat; Grover, Ankit (International Journal of Research in Medical Sciences, 2020)
Background: Diabetes Mellitus is a metabolic disorder characterized by hyperglycemia with disturbances of carbohydrate, lipid as well as protein metabolism virtually affecting every organ in the human body. Dyslipidemia is a group of biochemical disorders, which is frequently seen in diabetic individuals. Dyslipidemia associated with diabetes has a major role in atherosclerosis and cardiovascular complications. Methods: This cross-sectional study was conducted in diabetic patients visiting OPD of Shri Ram Murti Smarak Institute of Medical Sciences, Bareilly over a period of 6 months. A total of 320 patients were randomly selected for the study and divided into 2 groups depending on HbA1c levels. Results: BMI of controlled diabetics was 26.2±1.91 kg/m2 and of uncontrolled was 27.56±4.36 kg/m2 respectively with a statistically significant p value. Total Cholesterol levels in controlled group was 185.63±52.32 mg% and 217.83±61.33 mg% in uncontrolled group with a p value of 0.0005 which is highly significant. Same was seen in triglyceride and VLDL levels in controlled group which was 173.88±101.77 mg% and 31.5±12 mg% respectively and 203.33±83.7 mg% and 40.67±17.66 mg% in uncontrolled group respectively. Conclusions: The diabetic patients with poor glycemic control had statistically significant high values of Total Cholesterol, Triglycerides, VLDL levels and significant low HDL Levels. Good glycemic control can result in improvement in the lipid panel and the patients can be prevented from the high cardiovascular and neurological risk.